Horizontal solid burning under laminar forced convection and turbulent buoyant convection with an unheated segment. (May 2022) - Zhang, Yue; Fang, Jun; Tu, Ran; Song, Lei; Singh, Ajay V.
Abstract: In this paper, the effect of an unheated starting length, L 0 varying between 0 and 30 cm, on the burning and heat transfer characteristics over a horizontal Poly (methyl methacrylate) flat plate is experimentally investigated under wind velocities ranging from 0.5–2.0 m/s. The flame images, flame standoff distance, and Nusselt number are measured or calculated. In comparison to the wind velocity, the effect of an unheated starting length is of first-order importance in influencing the flow, heat transfer, and combustion over a solid fuel surface. The unheated segment introduces unique streamwise streaky flames. A critical condition is found to exist at L 0  = 10 cm, where the spanwise wave and lattice structures are observed in the flame, causing the standoff distance and Nusselt number to increase markedly beyond the theoretical prediction. When the unheated segment exceeds a certain length, the increased unheated length effect becomes negligible. Furthermore, the unheated segment shortens the laminar forced convection region and broadens the turbulent buoyant convection region. The study provides very crucial information regarding the effects of an unheated segment on the transitioning mechanism of a wind-driven flame which might be useful and important for fire research.